Empowering Self-Realization of Terrorism Clients with a Family System Therapy Approach : Case Study at Correctional Center Class I Tangerang - Sasgin Azahra; Muhammad Ali Equatora; Qisthina Aulia; Herry Fernandez Butar-Butar (CV. ULIL ALBAB CORP, 2024)
Terrorism remains a frightening specter in society, with around 80% of former terrorism convicts still experiencing cognitive errors. This serves as the basis that former terrorism convicts must have a positive self-realization and be able to develop their potential to live during the social reintegration period. The purpose of this research is to understand the process of self-actualization empowerment for terrorism clients using the family system therapy approach at the Correctional Center Class I Tangerang and the obstacles that hinder this process. This research uses a qualitative approach, with a case study design, involving direct interviews with several informants and observations. The research results show that the process of empowering the self-realization of terrorism clients occurs through three stages: family cohesion, flexibility, and communication. Self-realization is achieved through meaning-making, self-determination, influence, and competence. At the peak of self-realization, clients achieve social growth, self-fulfillment through training, achievement of potential through work, and encouragement from the spiritual and moral values they adhere to. The obstacles hindering the empowerment process are the limitations of nonverbal communication, distrust of newcomers, and lack of participation from family members. The findings of this research are important as a source of enhancing the credibility of the Directorate General of Corrections in the eyes of the public.